Formal Concept Analysis with Constraints by EM Operators - Mao, Hua (Journal of the Indonesian Mathematical Society, 2017)
Formal concept analysis is a method of exploratory data analysis that aims at the extraction of natural cluster from object-attribute data tables. We present a way to add user's background knowledge to formal concept analysis. The type of background knowledge we deal with relates to relative importance of attributes in the input data. We introduce EM operators which constrain in attributes of formal concept analysis. The main aim is to make extraction of concepts from the input data more focused by taking into account the background knowledge. Particularly, only concepts which are compatible with the constraint are extracted from data. Therefore, the number of extracted concepts becomes smaller since we leave out non-interesting concepts. We concentrate on foundational aspects such as mathematical feasibility and computational tractability.